2020
DOI: 10.1016/j.imu.2020.100420
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lockdowns on the spread of COVID-19 in Saudi Arabia

Abstract: Epidemiological models have been used extensively to predict disease spread in large populations. Among these models, Susceptible Infectious Exposed Recovered (SEIR) is considered to be a suitable model for COVID-19 spread predictions. However, SEIR in its classical form is unable to quantify the impact of lockdowns. In this work, we introduce a variable in the SEIR system of equations to study the impact of various degrees of social distancing on the spread of the disease. As a case study, we apply our modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 25 publications
1
64
0
Order By: Relevance
“… 33 Mathematically, in very early stage of COVID-19 pandemic, the epidemiological model called Susceptible Infectious Exposed Recovered (SEIR) have been found as suitable model for COVID-19 spread predictions in Saudi Arabia. 34 They predicted number of infections can be lowered to 0.4 million by September 2020. This study demonstrates that, with a stricter level of lockdowns, the COVID-19 curve can be effectively flattened in Saudi Arabi.…”
Section: Impact Of Covid-19 On Urological Proceduresmentioning
confidence: 99%
“… 33 Mathematically, in very early stage of COVID-19 pandemic, the epidemiological model called Susceptible Infectious Exposed Recovered (SEIR) have been found as suitable model for COVID-19 spread predictions in Saudi Arabia. 34 They predicted number of infections can be lowered to 0.4 million by September 2020. This study demonstrates that, with a stricter level of lockdowns, the COVID-19 curve can be effectively flattened in Saudi Arabi.…”
Section: Impact Of Covid-19 On Urological Proceduresmentioning
confidence: 99%
“…A deterministic mathematical model based on susceptible, infectious, exposed, and recovered (SEIR) persons is developed to predict the COVID-19 outbreak. This model considers the effect of lockdown to estimate the number of affected people in Saudi Arabia [ 15 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, discrete epidemic models have been found appropriate for processing such data. See, for instance, [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ] and some related references therein. Studies on particular data for different countries or regions can be found in the literature related to COVID-19, sometimes related to public interventions, such as quarantines, isolation measures, lockdowns, use of masks, social distance rules, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on particular data for different countries or regions can be found in the literature related to COVID-19, sometimes related to public interventions, such as quarantines, isolation measures, lockdowns, use of masks, social distance rules, etc. See, for instance, those concerned with Saudi Arabia [ 16 , 17 ], Madrid capital town, metropolitan area and surrounding administrative area [ 18 , 19 ], India [ 23 , 24 ], Italy [ 25 ], United States [ 26 ], Canada and several of its provinces [ 28 ], Switzerland, [ 29 ], Brazil [ 30 ], etc. In addition, the analysis of data has been sometimes accompanied with mathematical analysis techniques on the pandemic evolution related to public interventions or mathematically founded analysis of the obtained data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation